Nu bli’r der ballade - Andersen, Harald (Kuml, 2001)
We’ll have trouble now! The Archaeological Society of Jutland was founded on Sunday, 11 March 1951. As with most projects with which P.V Glob was involved, this did not pass off without drama. Museum people and amateur archaeologists in large numbers appeared at the Museum of Natural History in Aarhus, which had placed rooms at our disposal. The notable dentist Holger Friis, the uncrowned king of Hjørring, was present, as was Dr Balslev from Aidt, Mr and Mrs Overgaard from Holstebro Museum, and the temperamental leader of Aalborg Historical Museum, Peter Riismøller, with a number of his disciples. The staff of the newly-founded Prehistoric Museum functioned as the hosts, except that one of them was missing: the instigator of the whole enterprise, Mr Glob. As the time for the meeting approached, a cold sweat broke out on the foreheads of the people present. Finally, just one minute before the meeting was to start, he arrived and mounted the platform. Everything then went as expected. An executive committee was elected after some discussion, laws were passed, and then suddenly Glob vanished again, only to materialise later in the museum, where he confided to us that his family, which included four children, had been enlarged by a daughter. That’s how the society was founded, and there is not much to add about this. However, a few words concerning the background of the society and its place in a larger context may be appropriate. A small piece of museum history is about to be unfolded. The story begins at the National Museum in the years immediately after World War II, at a time when the German occupation and its incidents were still terribly fresh in everyone’s memory. Therkel Mathiassen was managing what was then called the First Department, which covered the prehistoric periods. Although not sparkling with humour, he was a reliable and benevolent person. Number two in the order of precedence was Hans Christian Broholm, a more colourful personality – awesome as he walked down the corridors, with his massive proportions and a voice that sounded like thunder when nothing seemed to be going his way, as quite often seemed to be the case. Glob, a relatively new museum keeper, was also quite loud at times – his hot-blooded artist’s nature manifested itself in peculiar ways, but his straight forward appearance made him popular with both the older and the younger generations. His somewhat younger colleague C.J. Becker was a scholar to his fingertips, and he sometimes acted as a welcome counterbalance to Glob. At the bottom of the hierarchy was the student group, to which I belonged. The older students handled various tasks, including periodic excavations. This was paid work, and although the salary was by no means princely, it did keep us alive. Student grants were non-existent at the time. Four of us made up a team: Olfert Voss, Mogens Ørsnes, Georg Kunwald and myself. Like young people in general, we were highly discontented with the way our profession was being run by its ”ruling” members, and we were full of ideas for improvement, some of which have later been – or are being – introduced. At the top of our wish list was a central register, of which Voss was the strongest advocate. During the well over one hundred years that archaeology had existed as a professional discipline, the number of artefacts had grown to enormous amounts. The picture was even worse if the collections of the provincial museums were taken into consideration. We imagined how it all could be registered in a card index and categorised according to groups to facilitate access to references in any particular situation. Electronic data processing was still unheard of in those days, but since the introduction of computers, such a comprehensive record has become more feasible. We were also sceptical of the excavation techniques used at the time – they were basically adequate, but they badly needed tightening up. As I mentioned before, we were often working in the field, and not just doing minor jobs but also more important tasks, so we had every opportunity to try out our ideas. Kunwald was the driving force in this respect, working with details, using sections – then a novelty – and proceeding as he did with a thoroughness that even his fellow students found a bit exaggerated at times, although we agreed with his principles. Therkel Mathiassen moaned that we youngsters were too expensive, but he put up with our excesses and so must have found us somewhat valuable. Very valuable indeed to everyon e was Ejnar Dyggve’s excavation of the Jelling mounds in the early 1940s. From a Danish point of view, it was way ahead of its time. Therkel Mathiassen justly complained about the economic situation of the National Museum. Following the German occupation, the country was impoverished and very little money was available for archaeological research: the total sum available for the year 1949 was 20,000 DKK, which corresponded to the annual income of a wealthy man, and was of course absolutely inadequate. Of course our small debating society wanted this sum to be increased, and for once we didn’t leave it at the theoretical level.Voss was lucky enough to know a member of the Folketing (parliament), and a party leader at that. He was brought into the picture, and between us we came up with a plan. An article was written – ”Preserve your heritage” (a quotation from Johannes V. Jensen’s Denmark Song) – which was sent to the newspaper Information. It was published, and with a little help on our part the rest of the media, including radio, picked up the story.We informed our superiors only at the last minute, when everything was arranged. They were taken by surprise but played their parts well, as expected, and everything went according to plan. The result was a considerable increase in excavation funds the following year. It should be added that our reform plans included the conduct of exhibitions. We found the traditional way of presenting the artefacts lined up in rows and series dull and outdated. However, we were not able to experiment within this field. Our visions expressed the natural collision with the established ways that comes with every new generation – almost as a law of nature, but most strongly when the time is ripe. And this was just after the war, when communication with foreign colleagues, having been discontinued for some years, was slowly picking up again. The Archaeological Society of Jutland was also a part of all this, so let us turn to what Hans Christian Andersen somewhat provocatively calls the ”main country”. Until 1949, only the University of Copenhagen provided a degree in prehistoric archaeology. However, in this year, the University of Aarhus founded a chair of archaeology, mainly at the instigation of the Lord Mayor, Svend Unmack Larsen, who was very in terested in archaeology. Glob applied for the position and obtained it, which encompassed responsibility for the old Aarhus Museum or, as it was to be renamed, the Prehistoric Museum (now Moesgaard Museum).These were landmark events to Glob – and to me, as it turned out. We had been working together for a number of years on the excavation of Galgebakken (”Callows Hill”) near Slots Bjergby, Glob as the excavation leader, and I as his assistant. He now offered me the job of museum curator at his new institution. This was somewhat surprising as I had not yet finished my education. The idea was that I was to finish my studies in remote Jutland – a plan that had to be given up rather quickly, though, for reasons which I will describe in the following. At the same time, Gunner Lange-Kornbak – also hand-picked from the National Museum – took up his office as a conservation officer.The three of us made up the permanent museum staff, quickly supplemented by Geoffrey Bibby, who turned out to be an invaluable colleague. He was English and had been stationed in the Faeroe Islands during the war, where he learned to speak Danish. After 1945 he worked for some years for an oil company in the Gulf of Persia, but after marrying Vibeke, he settled in her home town of Aarhus. As his academic background had involved prehistoric cultures he wanted to collaborate with the museum, which Glob readily permitted. This small initial flock governed by Glob was not permitted to indulge inidleness. Glob was a dynamic character, full of good and not so good ideas, but also possessing a good grasp of what was actually practicable. The boring but necessary daily work on the home front was not very interesting to him, so he willingly handed it over to others. He hardly noticed the lack of administrative machinery, a prerequisite for any scholarly museum. It was not easy to follow him on his flights of fancy and still build up the necessary support base. However, the fact that he in no way spared himself had an appeasing effect. Provincial museums at that time were of a mixed nature. A few had trained management, and the rest were run by interested locals. This was often excellently done, as in Esbjerg, where the master joiner Niels Thomsen and a staff of volunteers carried out excavations that were as good as professional investigations, and published them in well-written articles. Regrettably, there were also examples of the opposite. A museum curator in Jutland informed me that his predecessor had been an eager excavator but very rarely left any written documentation of his actions. The excavated items were left without labels in the museum store, often wrapped in newspapers. However, these gave a clue as to the time of unearthing, and with a bit of luck a look in the newspaper archive would then reveal where the excavation had taken place. Although somewhat exceptional, this is not the only such case. The Museum of Aarhus definitely belonged among the better ones in this respect. Founded in 1861, it was at first located at the then town hall, together with the local art collection. The rooms here soon became too cramped, and both collections were moved to a new building in the ”Mølleparken” park. There were skilful people here working as managers and assistants, such as Vilhelm Boye, who had received his archaeological training at the National Museum, and later the partners A. Reeh, a barrister, and G.V. Smith, a captain, who shared the honour of a number of skilfully performed excavations. Glob’s predecessor as curator was the librarian Ejler Haugsted, also a competent man of fine achievements. We did not, thus, take over a museum on its last legs. On the other hand, it did not meet the requirements of a modern scholarly museum. We were given the task of turning it into such a museum, as implied by the name change. The goal was to create a museum similar to the National Museum, but without the faults and shortcomings that that museum had developed over a period of time. In this respect our nightly conversations during our years in Copenhagen turned out to be useful, as our talk had focused on these imperfections and how to eradicate them.We now had the opportunity to put our theories into practice. We may not have succeeded in doing so, but two areas were essentially improved:The numerous independent numbering systems, which were familiar to us from the National Museum, were permeating archaeological excavation s not only in the field but also during later work at the museum. As far as possible this was boiled down to a single system, and a new type of report was born. (In this context, a ”report” is the paper following a field investigation, comprising drawings, photos etc. and describing the progress of the work and the observations made.) The instructions then followed by the National Museum staff regarding the conduct of excavations and report writing went back to a 19th-century protocol by the employee G.V. Blom. Although clear and rational – and a vast improvement at the time – this had become outdated. For instance, the excavation of a burial mound now involved not only the middle of the mound, containing the central grave and its surrounding artefacts, but the complete structure. A large number of details that no one had previously paid attention to thus had to be included in the report. It had become a comprehensive and time-consuming work to sum up the desultory notebook records in a clear and understandable description.The instructions resulting from the new approach determined a special records system that made it possible to transcribe the notebook almost directly into a report following the excavation. The transcription thus contained all the relevant information concerning the in vestigation, and included both relics and soil layers, the excavation method and practical matters, although in a random order. The report proper could then bereduced to a short account containing references to the numbers in the transcribed notebook, which gave more detailed information. As can be imagined, the work of reform was not a continuous process. On the contrary, it had to be done in our spare hours, which were few and far between with an employer like Glob. The assignments crowded in, and the large Jutland map that we had purchased was as studded with pins as a hedge hog’s spines. Each pin represented an inuninent survey, and many of these grew into small or large excavations. Glob himself had his lecture duties to perform, and although he by no means exaggerated his concern for the students, he rarely made it further than to the surveys. Bibby and I had to deal with the hard fieldwork. And the society, once it was established, did not make our lives any easier. Kuml demanded articles written at lightning speed. A perusal of my then diary has given me a vivid recollection of this hectic period, in which I had to make use of the evening and night hours, when the museum was quiet and I had a chance to collect my thoughts. Sometimes our faithful supporter, the Lord Mayor, popped in after an evening meeting. He was extremely interested in our problems, which were then solved according to our abilities over a cup of instant coffee. A large archaeological association already existed in Denmark. How ever, Glob found it necessary to establish another one which would be less oppressed by tradition. Det kongelige nordiske Oldsskriftselskab had been funded in 1825 and was still influenced by different peculiarities from back then. Membership was not open to everyone, as applications were subject to recommendation from two existing members and approval by a vote at one of the monthly lecture meetings. Most candidates were of course accepted, but unpopular persons were sometimes rejected. In addition, only men were admitted – women were banned – but after the war a proposal was brought forward to change this absurdity. It was rejected at first, so there was a considerable excitement at the January meeting in 1951, when the proposal was once again placed on the agenda. The poor lecturer (myself) did his best, although he was aware of the fact that just this once it was the present and not the past which was the focus of attention. The result of the voting was not very courteous as there were still many opponents, but the ladies were allowed in, even if they didn’t get the warmest welcome. In Glob’s society there were no such restrictions – everyone was welcome regardless of sex or age. If there was a model for the society, it was the younger and more progressive Norwegian Archaeological Society rather than the Danish one. The main purpose of both societies was to produce an annual publication, and from the start Glob’s Kuml had a closer resemblance to the Norwegian Viking than to the Danish Aarbøger for nordisk Oldkyndighed og Historie. The name of the publication caused careful consideration. For a long time I kept a slip of paper with different proposals, one of which was Kuml, which won after having been approved by the linguist Peter Skautrup. The name alone, however, was not enough, so now the task became to find so mething to fill Kuml with. To this end the finds came in handy, and as for those, Glob must have allied him self with the higher powers, since fortune smiled at him to a considerable extent. Just after entering upon his duties in Aarhus, an archaeological sensation landed at his feet. This happened in May 1950 when I was still living in the capital. A few of us had planned a trip to Aarhus, partly to look at the relics of th e past, and partly to visit our friend, the professor. He greeted us warmly and told us the exciting news that ten iron swords had been found during drainage work in the valley of lllerup Aadal north of the nearby town of Skanderborg. We took the news calmly as Glob rarely understated his affairs, but our scepticism was misplaced. When we visited the meadow the following day and carefully examined the dug-up soil, another sword appeared, as well as several spear and lance heads, and other iron artefacts. What the drainage trench diggers had found was nothing less than a place of sacrifice for war booty, like the four large finds from the 1800s. When I took up my post in Aarhus in September of that year I was granted responsibility for the lllerup excavation, which I worked on during the autumn and the following six summers. Some of my best memories are associated with this job – an interesting and happy time, with cheerful comradeship with a mixed bunch of helpers, who were mainly archaeology students. When we finished in 1956, it was not because the site had been fully investigated, but because the new owner of the bog plot had an aversion to archaeologists and their activities. Nineteen years later, in 1975, the work was resumed, this time under the leadership of Jørgen Ilkjær, and a large amount of weaponry was uncovered. The report from the find is presently being published. At short intervals, the year 1952 brought two finds of great importance: in Februar y the huge vessel from Braa near Horsens, and in April the Grauballe Man. The large Celtic bronze bowl with the bulls’ heads was found disassembled, buried in a hill and covered by a couple of large stones. Thanks to the finder, the farmer Søren Paaske, work was stopped early enough to leave areas untouched for the subsequent examination. The saga of the Grauballe Man, or the part of it that we know, began as a rumour on the 26th of April: a skeleton had been found in a bog near Silkeborg. On the following day, which happened to be a Sunday, Glob went off to have a look at the find. I had other business, but I arrived at the museum in the evening with an acquaintance. In my diary I wrote: ”When we came in we had a slight shock. On the floor was a peat block with a corpse – a proper, well-preserved bog body. Glob brought it. ”We’ll be in trouble now.” And so we were, and Glob was in high spirits. The find created a sensation, which was also thanks to the quick presentation that we mounted. I had purchased a tape recorder, which cost me a packet – not a small handy one like the ones you get nowadays, but a large monstrosity with a steel tape (it was, after all, early days for this device) – and assisted by several experts, we taped a number of short lectures for the benefit of the visitors. People flocked in; the queue meandered from the exhibition room, through the museum halls, and a long way down the street. It took a long wait to get there, but the visitors seemed to enjoy the experience. The bog man lay in his hastily – procured exhibition case, which people circled around while the talking machine repeatedly expressed its words of wisdom – unfortunately with quite a few interruptions as the tape broke and had to be assembled by hand. Luckily, the tape recorders now often used for exhibitions are more dependable than mine. When the waves had died down and the exhibition ended, the experts examined the bog man. He was x-rayed at several points, cut open, given a tooth inspection, even had his fingerprints taken. During the autopsy there was a small mishap, which we kept to ourselves. However, after almost fifty years I must be able to reveal it: Among the organs removed for investigation was the liver, which was supposedly suitable for a C-14 dating – which at the time was a new dating method, introduced to Denmark after the war. The liver was sent to the laboratory in Copenhagen, and from here we received a telephone call a few days later. What had been sent in for examination was not the liver, but the stomach. The unfortunate (and in all other respects highly competent) Aarhus doctor who had performed the dissection was cal1ed in again. During another visit to the bogman’s inner parts he brought out what he believed to be the real liver. None of us were capable of deciding th is question. It was sent to Copenhagen at great speed, and a while later the dating arrived: Roman Iron Age. This result was later revised as the dating method was improved. The Grauballe Man is now thought to have lived before the birth of Christ. The preservation of the Grauballe Man was to be conservation officer Kornbak’s masterpiece. There were no earlier cases available for reference, so he invented a new method, which was very successful. In the first volumes of Kuml, society members read about the exiting history of the bog body and of the glimpses of prehistoric sacrificial customs that this find gave. They also read about the Bahrain expeditions, which Glob initiated and which became the apple of his eye. Bibby played a central role in this, as it was he who – at an evening gathering at Glob’s and Harriet’s home in Risskov – described his stay on the Persian Gulf island and the numerous burial mounds there. Glob made a quick decision (one of his special abilities was to see possibilities that noone else did, and to carry them out successfully to everyone’s surprise) and in December 1952 he and Bibby left for the Gulf, unaware of the fact that they were thereby beginning a series of expeditions which would continue for decades. Again it was Glob’s special genius that was the decisive factor. He very quickly got on friendly terms with the rulers of the small sheikhdoms and interested them in their past. As everyone knows, oil is flowing plentifully in those parts. The rulers were thus financially powerful and some of this wealth was quickly diverted to the expeditions, which probably would not have survived for so long without this assistance. To those of us who took part in them from time to time, the Gulf expeditions were an unforgettable experience, not just because of the interesting work, but even more because of the contact with the local population, which gave us an insight into local manners and customs that helped to explain parts of our own country’s past which might otherwise be difficult to understand. For Glob and the rest of us did not just get close to the elite: in spite of language problems, our Arab workers became our good friends. Things livened up when we occasionally turned up in their palm huts. Still, co-operating with Glob was not always an easy task – the sparks sometimes flew. His talent of initiating things is of course undisputed, as are the lasting results. He was, however, most attractive when he was in luck. Attention normally focused on this magnificent person whose anecdotes were not taken too seriously, but if something went wrong or failed to work out, he could be grossly unreasonable and a little too willing to abdicate responsibility, even when it was in fact his. This might lead to violent arguments, but peace was always restored. In 1954, another museum curator was attached to the museum: Poul Kjærum, who was immediately given the important task of investigating the dolmen settlement near Tustrup on Northern Djursland. This gave important results, such as the discovery of a cult house, which was a new and hitherto unknown Stone Age feature. A task which had long been on our mind s was finally carried out in 1955: constructing a new display of the museum collections. The old exhibitio n type consisted of numerous artefacts lined up in cases, accompaied ony by a brief note of the place where it was found and the type – which was the standard then. This type of exhibition did not give much idea of life in prehistoric times.We wanted to allow the finds to speak for themselves via the way that they were arranged, and with the aid of models, photos and drawings. We couldn’t do without texts, but these could be short, as people would understand more by just looking at the exhibits. Glob was in the Gulf at the time, so Kjærum and I performed the task with little money but with competent practical help from conservator Kornbak. We shared the work, but in fairness I must add that my part, which included the new lllerup find, was more suitable for an untraditional display. In order to illustrate the confusion of the sacrificial site, the numerous bent swords and other weapons were scattered a.long the back wall of the exhibition hall, above a bog land scape painted by Emil Gregersen. A peat column with inlaid slides illustrated the gradual change from prehistoric lake to bog, while a free-standing exhibition case held a horse’s skeleton with a broken skull, accompanied by sacrificial offerings. A model of the Nydam boat with all its oars sticking out hung from the ceiling, as did the fine copy of the Gundestrup vessel, as the Braa vessel had not yet been preserved. The rich pictorial decoration of the vessel’s inner plates was exhibited in its own case underneath. This was an exhibition form that differed considerably from all other Danish exhibitions of the time, and it quickly set a fashion. We awaited Glob’s homecoming with anticipation – if it wasn’t his exhibition it was still made in his spirit. We hoped that he would be surprised – and he was. The museum was thus taking shape. Its few employees included Jytte Ræbild, who held a key position as a secretary, and a growing number of archaeology students who took part in the work in various ways during these first years. Later, the number of employees grew to include the aforementioned excavation pioneer Georg Kunwald, and Hellmuth Andersen and Hans Jørgen Madsen, whose research into the past of Aarhus, and later into Danevirke is known to many, and also the ethnographer Klaus Ferdinand. And now Moesgaard appeared on the horizon. It was of course Glob’s idea to move everything to a manor near Aarhus – he had been fantasising about this from his first Aarhus days, and no one had raised any objections. Now there was a chance of fulfilling the dream, although the actual realisation was still a difficult task. During all this, the Jutland Archaeological Society thrived and attracted more members than expected. Local branches were founded in several towns, summer trips were arranged and a ”Worsaae Medal” was occasionally donated to persons who had deserved it from an archaeological perspective. Kuml came out regularly with contributions from museum people and the like-minded. The publication had a form that appealed to an inner circle of people interested in archaeology. This was the intention, and this is how it should be. But in my opinion this was not quite enough. We also needed a publication that would cater to a wider public and that followed the same basic ideas as the new exhibition. I imagined a booklet, which – without over-popularsing – would address not only the professional and amateur archaeologist but also anyone else interested in the past. The result was Skalk, which (being a branch of the society) published its fir t issue in the spring of 1957. It was a somewhat daring venture, as the financial base was weak and I had no knowledge of how to run a magazine. However, both finances and experience grew with the number of subscribers – and faster than expected, too. Skalk must have met an unsatisfied need, and this we exploited to the best of our ability with various cheap advertisements. The original idea was to deal only with prehistoric and medieval archaeology, but the historians also wanted to contribute, and not just the digging kind. They were given permission, and so the topic of the magazine ended up being Denmark’s past from the time of its first inhabitant s until the times remembered by the oldest of us – with the odd sideways leap to other subjects. It would be impossible to claim that Skalk was at the top of Glob’s wish list, but he liked it and supported the idea in every way. The keeper of national antiquities, Johannes Brøndsted, did the same, and no doubt his unreserved approval of the magazine contributed to its quick growth. Not all authors found it easy to give up technical language and express themselves in everyday Danish, but the new style was quickly accepted. Ofcourse the obligations of the magazine work were also sometimes annoying. One example from the diary: ”S. had promised to write an article, but it was overdue. We agreed to a final deadline and when that was overdue I phoned again and was told that the author had gone to Switzerland. My hair turned grey overnight.” These things happened, but in this particular case there was a happy ending. Another academic promised me three pages about an excavation, but delivered ten. As it happened, I only shortened his production by a third. The 1960s brought great changes. After careful consideration, Glob left us to become the keeper of national antiquities. One important reason for his hesitation was of course Moesgaard, which he missed out on – the transfer was almost settled. This was a great loss to the Aarhus museum and perhaps to Glob, too, as life granted him much greater opportunities for development.” I am not the type to regret things,” he later stated, and hopefully this was true. And I had to choose between the museum and Skalk – the work with the magazine had become too timeconsuming for the two jobs to be combined. Skalk won, and I can truthfully say that I have never looked back. The magazine grew quickly, and happy years followed. My resignation from the museum also meant that Skalk was disengaged from the Jutland Archaeological Society, but a close connection remained with both the museum and the society. What has been described here all happened when the museum world was at the parting of the ways. It was a time of innovation, and it is my opinion that we at the Prehistoric Museum contributed to that change in various ways. The new Museum Act of 1958 gave impetus to the study of the past. The number of archaeology students in creased tremendously, and new techniques brought new possibilities that the discussion club of the 1940s had not even dreamt of, but which have helped to make some of the visions from back then come true. Public in terest in archaeology and history is still avid, although to my regret, the ahistorical 1960s and 1970s did put a damper on it. Glob is greatly missed; not many of his kind are born nowadays. He had, so to say, great virtues and great fault s, but could we have done without either? It is due to him that we have the Jutland Archaeological Society, which has no w existed for half a century. Congr tulat ion s to the Society, from your offspring Skalk. Harald Andersen Skalk Magazine Translated by Annette Lerche Trolle